Human trafficking and smuggling of migrants : the international instruments and domestic laws of Malaysia - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
Human trafficking and smuggling of migrants is a global problem. It is a major crime against humanity and a sheer violation of the basic human rights. It involves illegal trade of human beings for commercial purposes such as sexual exploitation, prostitution, slavery, servitude, forced labour or illegal organ removal. People are being bought, sold and are transported, transferred, harboured or received through use of force, coercion or other means for the purpose of exploitation and this problem is faced by most of the third world countriesHaving said the above, this chapter discusses the international instruments and domestic laws of Malaysia on human trafficking and smuggling of migrants with reference to decided cases. Further, some reference is made to the Islamic approach on this subject. At this juncture, it would be worthwhile to note that exploitation, oppression and wrongdoing, amongst others, are forbidden by the Qur’an and the Sunnah of the Prophet (p.b.u.h.), the primary sources of Islamic law.